Embodying Military Muscles and a Remasculinized West: Influencer Marketing, Fantasy, and "the Face of NATO". Issue 1 (10th March 2022) - Hedling, Elsa; Edenborg, Emil; Strand, Sanna
Abstract: In 2018, North Atlantic Treaty Organization (NATO) carried out Trident Juncture, its largest military exercise since the Cold War. The event was promoted on social media featuring Lasse Matberg as "the face of NATO." Matberg is an Instagram influencer, model, and lieutenant in the Royal Norwegian Navy, with an impressive physique and Viking looks. He frequently appears on NATO's social media accounts and lends his own platform to share activities such as working out with the Secretary-General. Drawing on the notion of "fantasmatic logics", we study how visual narratives of influencer marketing can contribute to making war preparations appear normal, void of political significance and even desirable. The figure of Lasse Matberg is read in conjunction with international rearmament and increasing geopolitical antagonism bound up with ideas of "traditional masculinity" and "feminization." We argue that the muscular yet ambiguously "soft" figure of Lasse Matberg projects a symbolic remasculinization of the West, operating through a fantasmatic logic that seemingly reconciles the contradiction between a West, which is imperial and militarily muscular on the one hand and caring, democratic, and progressive on the other. By shedding light on NATO's use of influencer marketing to promote a military exercise, this article contributes novel insights into the ways in which the figure of the NATO soldier and NATO military buildup are produced as appealing, allowing an ambivalent gendered geopolitical imaginary to emerge.